Emerging environmental Multi-Level Governance in China? Environmental protests, public participation and local institution-building. (April 2019) - Hensengerth, Oliver; Lu, Yiyi
Chinese state reforms have resulted in both horizontal and vertical diffusion of actors in policy-making and policy implementation, leading to the creation of new collaborative institutions between government and non-government actors. At the non-governmental level, this has inter alia enabled the development of non-governmental organizations and the passage of a raft of legislation for public participation and access to information. However, the political and legal constraints imposed by the authoritarian system have meant that private citizens still find it hard to make their voice heard. Public participation legislation has suffered from an implementation gap, leading to the proliferation of environmental protests across China. For private citizens, therefore, protest outside of the formal-legal channels is a key tool to influence the policy process and demand public participation and better government accountability. There are indications that protests may result in the improvement and creation of local institutions that facilitate public participation, which in turn help to foster a new model of governance that contains features of Multi-Level Governance.